Chapter 4 Brothers as Partners Centrifugal Federalism, Confederal Citizenship and Complicated Partnership - Štiks, Igor (Bloomsbury Academic, 2015)
Between 1967 and 1974 Yugoslavia entered a period of intensive constitutional changes that started with a series of amendments to the 1963 Constitution and ended with the adoption of a new, fourth in less than 30 years, Yugoslav Constitution in 1974. These changes transformed the country into a confederation of republics by transferring ever more powers from the federal centre to the subunits. It soon reached the point of making the centre dependent on consensus among quasi-independent republics, empowered even with certain prerogatives usually reserved for sovereign states. Centrifugal federalism describes this system of progressively empowering the subunits to the point of a break-up. The hybrid structure of Yugoslavia was also manifested in the constitutional definitions of federal and republican citizenship. The political primacy of the republics shifted the centre of citizen's political activity towards his or her republic. Although republican-level citizenship was almost practically irrelevant for ordinary citizens in their everyday life, politically speaking it was republican belonging and citizenship that increasingly took the leading role.